Zaprzepaszczone szanse Aktu o Usługach Cyfrowych? – rozważania dotyczące definicji platformy internetowej - część 1 - Doniec-Niezgoda, Justyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2024)
The article is divided into two parts. In the first one, the author discusses the objectives of the Digital Services Act, which are relevant to understanding the definition of an “online platform” and evaluating the regulations introduced. The author then begins to analyze the component definitions of an “online platform”, which include the concepts of an information society service (1) and a hosting service that stores and disseminates information to the public (2). The second of the component definitions of an “online platform”, is discussed in detail in the next part of the article. The meaning of the concept of dissemination to the public of information within the meaning of the DSA and the provision of a service at the “individual request of the recipient” of this service was developed. For a comprehensive analysis, it was also necessary to look at the exclusion implicit in the definition of an „online platform” in Article 3(i) of the DSA, concerning the minor and purely ancillary feature of the service of storing and disseminating information to the public at the request of the recipient of the service comparing to other services offered by the provider in question. At the end of the second part of the article, the author draws conclusions about the whole two parts of the article.
Keywords: Digital Services Act; DSA; online platform; intermediary service; hosting service